Experimental investigation on the thermal performance of a water-cooled loop thermosyphon system under fan failure conditions. (April 2021) - Zou, Sikai; Zhang, Quan; Ling, Li; Wang, Jiaqiang; Ma, Xiaowei; Du, Sheng; Yue, Chang
Highlights: A water-cooled loop thermosyphon system (LTS) is studied under fan failure conditions. The effects of fan failures on the thermal performance are analyzed and evaluated. The anti-failure capability at different filling ratios are compared. It is better to choose a high optimal filling ratio to ensure the good operating performance and anti-failure capability of LTS. Abstract: Fan failure of water-cooled loop thermosyphon system (LTS) is a major factor for thermal safety of data center, thus it is necessary to investigate the effects of fan failures on the thermal performance. In this paper, different operating conditions including normal and eight possible fan failure modes of a LTS are tested at various refrigerant filling ratios. The optimal refrigerant filling ratio is ranged from 55.8% to 74.4% under normal operating condition. Compared with the conditions of leakage (Filling ratio = 46.5%) or overcharge (Filling ratio=83.7%), the LTS has better anti-failure capability with an optimal filling ratio. The cooling capacity at 55.8% filling ratio decreases by 8.2–10.1% and 20.8–23.8% under mild and serious fan failure modes, respectively, and the decrements increase with the filling ratio increasing. This is because the additional refrigerant mass flow rate increases with the filling ratio increasing, which increases the total system thermal resistance. However, the cooling capacity at the minimum optimal filling ratio (55.8%) is only 9.6% larger than that at the maximum optimal filling ratio (74.4%) under the worst fan failure condition. Considering the universality of the slight refrigerant leakage in refrigeration systems, it is better to choose a high optimal filling ratio to ensure the good operating performance and anti-failure capability of LTS.